Revealed comparative advantages in Greece, Ireland, Portugal and Spain - Jens Oelgemöller (Intereconomics, 2013)
Greece, Ireland, Portugal and Spain were all hit by the economic downturn in the course of the financial crisis and have been struggling with national debt crises and recession. A problem common to all of these countries is the collapse of national demand. Foreign trade might seem a logical way to restore economic strength, but little is known about the international competitiveness of these countries' industries. This paper sheds light on their export structures using the revealed comparative advantage indicator.
Keywords: 330; Komparativer Vorteil; Außenhandel; Außenhandelsstruktur; Griechenland; Irland; Portugal; Spanien